Low-intensity repetitive paired associative stimulation targeting the motor hand area at theta frequency causes a lasting reduction in corticospinal excitability. Issue 10 (October 2020) - Rizzo, V.; Mastroeni, C.; Maggio, R.; Terranova, C.; Girlanda, P.; Siebner, H.R.; Quartarone, A.
Highlights: 5-Hz rPAS25ms produces a long-lasting increase in corticospinal excitability. 5-Hz rPAS15ms effectively suppresses corticospinal excitability. 5-Hz rPAS induces spike-timing dependent plasticity-like bidirectional plasticity. Abstract: Objective: Sub-motor threshold 5 Hz repetitive paired associative stimulation (5 Hz-rPAS25ms ) produces a long-lasting increase in corticospinal excitability. Assuming a spike-timing dependent plasticity-like (STDP-like) mechanism, we hypothesized that 5 Hz-rPAS at a shorter inter-stimulus interval (ISI) of 15 ms (5 Hz-rPAS15ms ) would exert a lasting inhibitory effect on corticospinal excitability. Methods: 20 healthy volunteers received two minutes of 5 Hz-rPAS15ms . Transcranial magnetic stimulation (TMS) was applied over the motor hotspot of the right abductor pollicis brevis muscle at 90% active motor threshold. Sub-motor threshold peripheral electrical stimulation was given to the left median nerve 15 ms before each TMS pulse. We assessed changes in mean amplitude of the unconditioned motor evoked potential (MEP), short-latency intracortical inhibition (SICI), intracortical facilitation (ICF), short-latency afferent inhibition (SAI), long-latency afferent inhibition (LAI), and cortical silent period (CSP) before and for 60 minutes after 5-Hz rPAS15ms . Results: Subthreshold 5-Hz rPAS15ms produced a 20–40% decrease in mean MEP amplitude along with an attenuation in SAI, lasting at least 60 minutes. A follow-up experiment revealed that MEP facilitation was spatially restricted to the target muscle. Conclusions: Subthreshold 5-Hz rPAS15ms effectively suppresses corticospinal excitability. Together with the facilitatory effects of subthreshold 5-Hz rPAS25ms (Quartarone et al., J Physiol 2006;575:657–670), the results show that sub-motor threshold 5-Hz rPAS induces STDP-like bidirectional plasticity in the motor cortex. Significance: The results of the present study provide a new short-time paradigm of long term depression (LTD) induction in human sensory-motor cortex.